EXPLORING STUDENTS VOCABULARY MASTERY THROUGH PHOTOGRAPH - Yayah Nurhidayah Rahman (Universitas Majalengka, 2021)
The use of media in teaching and learning is needed. It gives an effect toward the learning outcome. Inappropriate teaching media made a new problem; the teaching and learning was not effective, wasting time and cost. Therefore, the lecturer must catch a special media to overcome the students’ problem regarding learning vocabulary. In this research, the teacher did a classroom action research by using two cycles; Planning, Implementing, Observing and reflecting with three meetings in every single cycle. The research was conducted with the purposes: 1) to explore the vocabulary mastery catch by students of civil engineering by using photograph ,2) to find out the students responses toward using photograph in learning vocabulary. The subject of the research was the students of civil engineering. In obtaining an actual data the researcher used descriptive analysis toward documentation, score list and observation checklist. After data have been analyzed, the result showed that using photograph as teaching media was effective. They got 79.00 % in the first cycle and got better score in the next cycle with average 87.00 %. Finally, the hypothesis proposed in this research was accepted. In conclusion, Photograph is the appropriate media in exploring students' vocabulary mastery through students of civil engineering